A study on effectiveness process development of safety’s poster design for pedestrian user / Insyirah Izzliyana Sulaiman - Sulaiman, Insyirah Izzliyana (2019)
A pedestrian can be anyone who is travelling by walking in the public areas or spaces. Walking can be classified as one of the main ways of transportation for human movement. Everyday thousands of people are killed and injured on the roads. Various aspects and factors that lead to the accident among the pedestrian and other road users are needed to be studied, so that the safety for all road user should be improved. There are type of pedestrian who crosses the street and mostly such crashes happen when the pedestrian crosses the street, and many seem to result from pedestrian heedlessness. Thus, when pedestrians are using mobile phones, distracted attention may increase their risk of accidents. From the research and survey that have been done, I found out that there are a few factors that cause an accident happen toward pedestrian that actually causes from themselves. The rest is, carelessness of the pedestrian while crossing the road, pedestrian did not respect the law for road safety and not using the facilities and pedestrian do not use the facilities that government have provide for them to facilitate pedestrians crossing easy to cross such as bridge for pedestrian and zebra crossing. In order to enhance the government efforts to mitigate road accidents, it is efficient to use an education as a medium which helps to change the attitude of road users in the country. Therefore, awareness of pedestrian crossing needs to be continued to raise the awareness about road safety.